Suicidal thoughts among university students: The role of mattering, state self-esteem and depression level - Kususanto Ditto Prihadi; Charon Y.S. Wong; Erina Y.V. Chong; Kate Y.X. Chong (International Journal of Evaluation and Research in Education (IJERE), 2020)
The protective role of mattering on suicide ideation among university students was examined. Our study is grounded in the Interpersonal-Psychological Theory of Suicide, which led to a hypothesis that between depression levels and state self-esteem has significant serial multiple mediating effects on the relationship between mattering and suicide ideation. University students from various nationality who study in Indonesia and Malaysia (n=509) responded to General Mattering Scale, State Self-Esteem Scale, Beck’s Depression Inventory, and Suicide Ideation Attributes Scale, as well as demographic details including their gender, spirituality, education, birth order and nationality. The result of Bootstrap analyses with 95% confident interval from 5000 samples suggested that the serial mediation partially occurred to the link between mattering and suicide ideation.